The Role of Social Media Applications During the COVID-19 Pandemic in Improving Administrative Communication among the University of Tabuk Employees from the Academics and Employees Point of View (WhatsApp as a Model) - Khalifah Hammad Albalawi (Deanship of Scientific Research (DSR), the University of Jordan, 2023)
Objectives: The study aimed to reveal the role of using social media applications (WhatsApp) during the COVID-19 pandemic in improving administrative communication among workers at the UT, and to reveal the differences between the sample responses according to variables: type, nature of work, years of service at the university. Methods: the descriptive survey method and the questionnaire were used to collect data. The study population consisted of all academics and administrators working at the UT amounting (to 2654) individuals, and the sample included (336) individuals. Results: The results showed that the level of the role of social media applications (WhatsApp) during the pandemic in improving administrative communication among university employees was generally high and in the four dimensions. The results also showed that there were significant differences at the level (α ≥ 0.05) between the average responses of the study sample to the study tool due to the nature of the work variable, while there were no significant differences due to the gender variable and the years of service at the university variable. Conclusions: The study recommended the need to provide the necessary data to solve problems in the work environment to facilitate the decision-making process.